PEMANFAATAN MEDIA GAMBAR ILUSTRASI DALAM PEMBELAJARAN MENULIS CERPEN: ANALISIS UNSUR INTRINSIK PADA KARYA SISWA SMA - Agustina, Putri Esa; Irfai Fathurohman; Ristiyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The ability to write short stories is an important skill that needs to be developed in students. However, many students experience difficulties in generating ideas and developing narrative elements in their writing. One of the learning media that can help stimulate students’ imagination is illustrated images. This study aims to analyze the intrinsic elements of students’ short stories written based on illustrated images. The research used a descriptive qualitative approach. The data sources were several short stories written by students of class XI at SMA Negeri 1 Mejobo which were produced after the use of illustrated images in the learning process. Data were collected through documentation of students’ written works and analyzed by examining the intrinsic elements of the short stories, including theme, plot, character, setting, and language use. The results of the study show that illustrated images can help students develop story ideas more easily and direct the development of narrative elements in their writing. The short stories produced by students generally demonstrate clearer themes, more structured plot development, more detailed character descriptions, and richer settings. In addition, the use of illustrated images encourages students to express emotions and conflicts in a more creative way. Therefore, illustrated images can be used as an effective medium to stimulate students’ imagination and support the development of intrinsic elements in short story writing.